Analysis of the Role of the Inspectorate in Supervision of Village Funds in Deli Serdang Regency - Melsa Siagian; Nur Ahmadi Bi Rahmani (Penerbit Jurnal Indonesia, 2022)
This study aims to determine and analyze the description of the implementation of the role and function of the inspectorate in supervising village funds in the Deli Serdang Regency as well as the obstacles faced by the villages in the Deli Serdang Regency. Technically this method uses a descriptive method with a qualitative approach, namely by describing it operational activities and plays carried out by the deli Serdang district inspectorate, thus the data sources are people or supervisors. The results of the study conclude that the supervisory role through internal audits of village fund organizers in Deli Serdang district has been carried out well, although there are also some weaknesses regarding the organizers. Village Funds in Deli Serdang Regency.